2016
DOI: 10.7166/27-4-1549
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Establishing a Human Asset Register for the Improved Management of People in Physical Asset Management

Abstract: People are fundamental to the success of managing physical assets. Line managers are increasingly becoming responsible for peoplemanagement activities that were traditionally placed within the human resources function, while often lacking effective peoplemanagement skills. A framework was developed to establish a human asset register to support asset managers in improving the management of people. The proposed framework provides a generic step-based approach to establishing a structured reflection of human dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
9
1
Order By: Relevance
“…Many key findings and contributions ensue from the AHP analysis, and they can be summarized as follows. First, the study revealed that not all factors are viewed as having equal importance in improving PAM performance, as was reported by previous studies and this finding is a novelty of study (Draganidis and Mentzas, 2006; Jooste and Vlok, 2015; Kriege et al , 2016; Xerri et al , 2013; Zuashkiani et al , 2011).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Many key findings and contributions ensue from the AHP analysis, and they can be summarized as follows. First, the study revealed that not all factors are viewed as having equal importance in improving PAM performance, as was reported by previous studies and this finding is a novelty of study (Draganidis and Mentzas, 2006; Jooste and Vlok, 2015; Kriege et al , 2016; Xerri et al , 2013; Zuashkiani et al , 2011).…”
Section: Discussionmentioning
confidence: 51%
“…This result supports previous studies which stated that the performance of asset management is influenced by and dependent on people, how they are managed and the understanding of human dimensional characteristics. Previous studies have also found that people are most fundamental to success in managing physical assets (Kriege et al , 2016). They have emphasized that employees and leadership are equally as important as the PAM system itself (Schoeman and Vlok, 2014), and have shown that the human dimension determines the effectiveness and success of PAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 2000s, a general agreement about a holistic view of physical asset management (AM) became prevalent in engineering circles. It emphasised lifecycle AM, the strategic planning of an AM strategy, asset risk management, optimisation, and other factors of AM such as human, safety, and environmental factors [13,14]. As the discipline matured, practitioners became insightful and, recently, have better understood that AM refers to the use of 'assets' to realise value and achieve explicit organisational purposes rather than the mere thought of "doing things to assets" [15].…”
Section: Theoretical Backgroundmentioning
confidence: 99%